2007
DOI: 10.1128/aem.01370-07
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Detection of Human Viruses and Coliphage in Newport Bay, California

Abstract: Recent studies have shown that the fecal indicator bacteria (FIB) currently used to indicate water quality in the coastal environment may be inadequate to reflect human viral contamination. Coliphage was suggested as a better indicator of human viral pollution and was proposed by the U.S. EPA as an alternative indicator for fecal pollution in groundwater. In this study, we investigated the occurrence and distribution of FIB, F؉ coliphage, and PCRdetectable human adenovirus and enterovirus for an entire year at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 33 publications
3
36
0
5
Order By: Relevance
“…Thus, many studies have failed to show any correlation in fresh surface waters [133][134][135][136][137], marine surface water [136][137][138], and groundwater [131,139]. In contrast, other studies have shown some correlation between human viruses and F-specific phages [23,123,126,140,141] and between human viruses and somatic coliphages in surface waters [104,140,142], between enteroviruses and somatic coliphages in sludge [82], and between human viruses and both somatic and F-specific phages in surface water [78].…”
Section: Relationship To Human Virusesmentioning
confidence: 93%
See 1 more Smart Citation
“…Thus, many studies have failed to show any correlation in fresh surface waters [133][134][135][136][137], marine surface water [136][137][138], and groundwater [131,139]. In contrast, other studies have shown some correlation between human viruses and F-specific phages [23,123,126,140,141] and between human viruses and somatic coliphages in surface waters [104,140,142], between enteroviruses and somatic coliphages in sludge [82], and between human viruses and both somatic and F-specific phages in surface water [78].…”
Section: Relationship To Human Virusesmentioning
confidence: 93%
“…In groundwater these failures have been identified for enteroviruses, rotaviruses, hepatitis-A viruses, and noroviruses [131,139]; noroviruses, enteroviruses, rotaviruses, adenoviruses, and hepatitis-A viruses [129]; enteroviruses and noroviruses [127]; and enteroviruses, adenoviruses, and reoviruses [143]. In surface waters, a lack of co-occurrence or correlation has been reported for adenoviruses and enteroviruses [136]; enteroviruses and adenoviruses [142]; enteroviruses and adenoviruses [124]; adenoviruses and noroviruses [144]; and enteroviruses and polyomaviruses [145]. In contrast, some studies on surface waters have shown correlations among different pathogenic viruses, such as astroviruses, noroviruses, rotaviruses, and adenoviruses [23]; enteroviruses, reoviruses, noroviruses, and rotaviruses [78]; and adenoviruses and noroviruses [141].…”
Section: Relationship To Human Virusesmentioning
confidence: 99%
“…Host-specific markers, targeting 16S rDNA and other genes, have been identified for E coli 43,57,58) , methanogens 100,101) , viruses and coliphage 52,59) , member of the Bacteriodales 32,62,78,89) , and metagenomic DNA fragments 91,92) . However, before use in field studies these host-specific markers need to be validated by estimating the proportion of false-positives and false-negatives in the target population, and for sensitivity in detecting these bacteria that are present in low numbers in complex matrices, such as soil and sediment.…”
Section: Microbial Source Trackingmentioning
confidence: 99%
“…Library-independent MST methods employ host-specific markers, including PCR primers 32,52,[57][58][59]62,78,89,91,92) and gene probes 43,94) , to determine sources of fecal pollution. Host-specific markers, targeting 16S rDNA and other genes, have been identified for E coli 43,57,58) , methanogens 100,101) , viruses and coliphage 52,59) , member of the Bacteriodales 32,62,78,89) , and metagenomic DNA fragments 91,92) .…”
Section: Microbial Source Trackingmentioning
confidence: 99%
“…In general, any microbial contamination of water sources is a probable health concern and needs to be monitored closely. This is because contaminated water could harbor a variety of pathogens, such as Escherichia coli, Salmonella, Shigella, Campylobacter, Yersinia, Vibrio, enterovirus, norovirus, adenovirus, coxsackievirus, echovirus, and hepatitis A and E viruses (HAV, HEV), Schistosoma, Dracunculus medinensis, Echinococcus granulosus, Entamoeba histolytica, Cryptosporidium parvum, and Giardia lamblia [5][6][7][8][9][10][11].…”
Section: Pathogens In Watermentioning
confidence: 99%